Medial Arm Perforator Flaps – A Cadaveric Study - DaisySahni, Richa Gupta, Sunil Gaba, (International Journal of Scientific Research and Management (IJSRM), 2014)
The goal of any reconstructive surgery is to resurface the defects with a pliable and cosmetically similar tissue thatwill allow accurate function. Perforator flaps can be tailored to accurately reconstruct the defect, including flapthinning for resurfacing shallow defects. They offer reliable blood supply just like musculocutaneous flapsas well asreduced donor-site morbidity. Medial surface of distal arm has been described as a potential donor site for theperforator flaps because of its excellent color and fine texture. The territory of medial arm is relatively unexploredregion. Data providing information regarding consistent site of perforator, main source vessel supplying it, totalnumber of perforators as well as location of perforators in relation to fixed bony landmarks in the region of medialsurface of arm is sparse. This cadaveric study showed that the brachial artery (BA) is the main source vessel (71.4%cases) supplying most of the perforators of medial arm region. Also, consistent site of perforator was describedwithin region of 115.8 mm proximal and 16.8 mm medial to the medial epicondyle within a circle of 23.8 mm. Theseobservations are useful to use the medial surface of the arm as donor site area in reconstructive surgery procedures.